2006
DOI: 10.1002/ijc.22448
|View full text |Cite
|
Sign up to set email alerts
|

Prospective study of vitamins C, E, and A and carotenoids and risk of oral premalignant lesions in men

Abstract: Case-control studies indicate that vitamins C, E, A and carotenoids decrease risk of oral premalignant lesions (OPLs) and oral cancer, but clinical trials have failed to find protective effects of bcarotene and suggest that vitamin E may increase risk. The authors prospectively evaluated the association between intake of vitamins C, E, A and carotenoids and incidence of OPL. Participants were 42,340 men in the Health Professionals Follow-up Study who provided information on supplement use and diet every 2-4 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 56 publications
0
14
0
2
Order By: Relevance
“…Moreover, the emerging evidence suggests that very high doses of antioxidant vitamins may not be beneficial for health and might even be harmful. Indeed, clinical trials of vitamins E, C, and A have failed in patients with a range of disorders (Hasnain and Mooradian, 2004;Block et al, 2007;Canter et al, 2007;Maserejian et al, 2007;Galasko et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the emerging evidence suggests that very high doses of antioxidant vitamins may not be beneficial for health and might even be harmful. Indeed, clinical trials of vitamins E, C, and A have failed in patients with a range of disorders (Hasnain and Mooradian, 2004;Block et al, 2007;Canter et al, 2007;Maserejian et al, 2007;Galasko et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…For example, in other studies of the participants in the Health Professsionals Follow-up Study, no association was observed between lycopene intake and the risk of oral premalignant lesions [69] or between tomato consumption and the risk of bladder cancer [70]. In a pooled analysis of food frequency questionnaires from 11 cohort studies including more than 700,000 participants and 7,885 incident cases of colorectal cancer, tomato consumption was found to provide no reduction in the risk of colorectal cancer [71].…”
Section: Clinical Trialsmentioning
confidence: 99%
“…Further, some research has linked the consumption of lutein and zeaxanthin to reducing the risk for lung and breast cancer, although results are inconsistent [18,40]. The relationship between vitamins, carotenoid intake, and oral cancer risk has been studied [41]. Using dietary intake data from 42,340 men in the Health Professionals Follow-up Study, researchers determined the risk for oral premalignant lesions related to intake of vitamins A, C, and E, and carotenoids from food or dietary supplements.…”
Section: Global Health Benefits Associated With Glvsmentioning
confidence: 97%